2004
DOI: 10.1073/pnas.0400628101
|View full text |Cite
|
Sign up to set email alerts
|

Purification and architecture of the ubiquitous Wave complex

Abstract: The Wave proteins are major activators of the Arp2͞3 complex. The ubiquitous Wave-2 is required for actin polymerization at the leading edge of migrating cells. Here we purify Wave-2 from HeLa cells. Five proteins, Sra, Nap, Wave-2, Abi, and Hspc, are copurified, indicating that they form a tight complex. These proteins are only present in the complexed form, with the exception of Hspc, which displays a free pool. We reconstitute the Wave-2 complex by cotranslating in vitro the five subunits and use this syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
294
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 213 publications
(308 citation statements)
references
References 23 publications
(28 reference statements)
13
294
1
Order By: Relevance
“…WRC is composed of five subunits, namely SCAR/WAVE, Sra1/ PIR121, Nap1, Abi and HSPC300 (Gautreau et al, 2004). In human cells, paralogous genes give rise to SCAR/WAVE1, WAVE2 and WAVE3, Sra1 and PIR121, and Abi1 and Abi2 to generate divergent WRC combinations.…”
Section: Resultsmentioning
confidence: 99%
“…WRC is composed of five subunits, namely SCAR/WAVE, Sra1/ PIR121, Nap1, Abi and HSPC300 (Gautreau et al, 2004). In human cells, paralogous genes give rise to SCAR/WAVE1, WAVE2 and WAVE3, Sra1 and PIR121, and Abi1 and Abi2 to generate divergent WRC combinations.…”
Section: Resultsmentioning
confidence: 99%
“…For example, mutant complementation tests indicate that human W/SRC and ARP2/3 complex subunits can substitute for the Arabidopsis proteins (Mathur et al, 2003b). Furthermore, biochemical assays of Arabidopsis W/SRC El-Assal et al, 2004;Frank et al, 2004;Le et al, 2006;Uhrig et al, 2007) and ARP2/ 3 assembly (Kotchoni et al, 2009) have shown that the binary interactions among W/SRC subunits and ARP2/3 complex assembly mechanisms are indistinguishable from those that have been observed for human W/SRC (Gautreau et al, 2004) and yeast ARP2/3 (Winter et al, 1999). After an initial period of controversy concerning the biochemical control of W/SRC, it is now apparent that vertebrate W/SRC (Derivery et al, 2009;Ismail et al, 2009), like the ARP2/3 complex (Machesky et al, 1999), is intrinsically inactive and requires positive regulation by Rac and other factors to fully activate ARP2/3 (Ismail et al, 2009;Lebensohn and Kirschner, 2009;Chen et al, 2010).…”
mentioning
confidence: 99%
“…Based on the equally severe syndrome of nap1 and arp2/3 null phenotypes, and double mutant analyses, the only known function of NAP1 is to positively regulate ARP2/3 (Brembu et al, 2004;Deeks et al, 2004;El-Din El-Assal et al, 2004;Li et al, 2004). The vertebrate SRA1-NAP1 dimer is important for W/SRC assembly (Gautreau et al, 2004) and forms an extended physical surface that trans-inhibits the C-terminal ARP2/3-activating domain of WAVE/SCAR . The plant NAP1 and SRA1 proteins share endto-end amino acid conservation with their vertebrate homologs and may form a heterodimer with similar functions El-Assal et al, 2004;Uhrig et al, 2007).…”
mentioning
confidence: 99%
“…If the Arabidopsis SCAR proteins identified function in a complex containing AtBRK1, then we could expect that they would bind directly to AtBRK1, because HSPC300 has been shown to bind directly to WAVE1 and WAVE2 (10,11). Therefore, full-length AtSCAR3 and AtSCAR1 were produced by in vitro transcription͞translation in the presence of [ 35 S]methionine together with T7 epitope-tagged AtBRK1 or two different T7-tagged negative control proteins (NC1 and NC2).…”
Section: Full-length Atscar Proteins and Their N-terminal Sh Domainsmentioning
confidence: 99%
“…However, recent work has identified plant homologs of three components of a mammalian WAVE-containing complex isolated from brain and HeLa cell extracts, which functions to regulate the localization and activity of WAVE͞Scar in vitro and in vivo (10)(11)(12). The first of these to be identified, BRK1, is a homolog of human HSPC300.…”
mentioning
confidence: 99%